Hubungan Antara Kepemimpinan Transformasional dan Iklim Komunikasi : Studi Kasus Dinas Perikanan Kabupaten Sikka - Fadila Fadila; Maria Rosa Dalima; Mikaela Glengan; Mikael Anjelo; Barnabas Kevin Keli (Universitas 45 Surabaya, 2025)
This study aims to analyze the relationship between transformational leadership and communication climate at the Sikka Regency Fisheries Service. Transformational leadership is seen as a leadership style capable of providing inspiration, motivation, exemplary behavior, and support for employee innovation. Meanwhile, organizational communication climate reflects employees' shared perceptions regarding the quality of internal communication, including support, trust, openness, and clarity of work goals. This study used a descriptive qualitative method with in-depth interviews with Fisheries Service employees. The results showed that transformational leadership was implemented quite well by the service leaders, as evidenced by exemplary behavior, inspiring motivation, individual attention, and encouragement to innovate. The organizational communication climate was also in the good category—marked by support among employees, trust in superiors, information transparency, and clear performance goals. The findings indicate a positive relationship where increasing the quality of transformational leadership strengthens the organizational communication climate. This study suggests the need for improvements in the distribution of technical information and strengthening two-way communication spaces.